2011
DOI: 10.1158/1055-9965.epi-10-1267
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Genotypes in Women with Cervical Precancer and Cancer at Kaiser Permanente Northern California

Abstract: Background The human papillomavirus (HPV) Persistence and Progression Cohort is a natural history study of carcinogenic HPV positive women. Here, we present the HPV genotypes found in first ∼500 cases of cervical intraepithelial neoplasia grade 3 (CIN3) or more severe disease (CIN3+) diagnosed at the study baseline. Methods Women aged 30 and older were screened for cervical cancer using Pap smears and tested for carcinogenic HPV using Hybrid Capture 2 (HC2; Qiagen). We randomly selected women who tested HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 34 publications
6
56
0
Order By: Relevance
“…Our results show a clear predominance of HPV16/18 attribution in CIN2þ lesions among all women in every racial/ethnic group, in agreement with other studies (6,11,12,17,(23)(24)(25). However, we found that compared with non-Hispanic white women, HPV31/33/45/52/58 contributes to a significantly higher proportion of CIN2þ in racial minorities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show a clear predominance of HPV16/18 attribution in CIN2þ lesions among all women in every racial/ethnic group, in agreement with other studies (6,11,12,17,(23)(24)(25). However, we found that compared with non-Hispanic white women, HPV31/33/45/52/58 contributes to a significantly higher proportion of CIN2þ in racial minorities.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, among the unvaccinated women, we found that HPV16/18 attribution was highest in the youngest age group and significantly decreased by age. The relatively lower proportions of HPV16/18-attributable lesions in the older group are congruent with epidemiologic evidence of stronger carcinogenic potential and faster progression of HPV16/ 18-associated lesions compared with lesions due to other highrisk types, and similar results have been shown in other studies (16,17,22,23).…”
Section: Discussionsupporting
confidence: 88%
“…Starting in 2007, the PaP cohort was created by collecting residual cervical specimens in specimen transport medium (STM) (Qiagen) from a majority of women who tested positive with the Hybrid Capture 2 (HC2) (e.g., it was not possible to process specimens testing positive on Friday afternoons), as well as a random sample of HPV-negative specimens (which were not considered in the present study). After the specimens were used for HC2 testing for clinical purposes, the residual specimens were neutralized and archived, as described below (15).…”
Section: Study Populationmentioning
confidence: 99%
“…Cases that were diagnosed directly following enrollment testing without an intervening second screen were considered prevalent. A random sample of HC2-positive women who had not been diagnosed as CIN2ϩ were chosen as prevalent controls, and all were typed by the laboratory of Robert Burk at the Albert Einstein College of Medicine in an extension of a previously reported prevalent case-control analysis (15). Cases that were diagnosed subsequent to enrollment (after a second screen) were considered incident and typed by Roche Molecular Systems at their research laboratory in Pleasanton, CA.…”
Section: Study Populationmentioning
confidence: 99%
“…18,19 The distribution of HPV genotypes between different grades of cytological atypia suggests that the risk of progression could be associated with HPV genotype. [20][21][22] HPV genotypes 16 or 18 are more likely to have an underlying CIN2+ or to progress faster to high-grade squamous intraepithelial lesion (HSIL) compared with other genotypes. 23,24 The understanding of HPV infection and the pathogenesis of cervical intraepithelial lesions and cancer has led to the development of several molecular markers aimed at differentiating transient from transforming HPV infections.…”
Section: Introductionmentioning
confidence: 99%